ChemInform Abstract: Recent Developments in Sulfur‐ and Selenium‐Catalyzed Oxidative and Isohypsic Functionalization Reactions of Alkenes. Issue 28 (July 2015) - Breder, Alexander; Ortgies, Stefan
Abstract Review: 62 refs.